(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2014)
تهدف الدراسة إلى توضيح المفهوم الاقتصادي لمشكلة التلوث البيئي والآثار الاقتصادية الناجمة عنه. وكيف تتم المواجهة الاقتصادية لهذه المشكلة من خلال اتباع الخطوات الآتية: 1- التقدير الكمي للتلوث البيئي (رصد نوعية الهواء في الوسط المحيط). 2- التقدير الكمي لنتائج التلوث البيئي (التأثير السلبي في الصحة والممتلكات بسبب تلوث الهواء, وخسائر الثروة الزراعية والحيوانية). 3- التقدير المالي لنتائج التلوث البيئي (تكاليف العلاج وفرص العمل البديلة, الخسارة في الناتج المحلي الإجمالي نتيجة عدم القدرة على العمل بسبب المرض أو العجز أو الموت المبكر, تكاليف الأضرار في الممتلكات وفي الثروة الزراعية والحيوانية, تكاليف الأضرار في القيمة الجمالية). وقد خلصت الدراسة إلى مجموعة من النتائج ومنها: - رصد واقع التلوّث في بانياس, ومن ثم مقارنة متوسط التكلفة التي يتحملها السكان نتيجة (الأضرار الصحية, الأضرار في الممتلكات, الأضرار في الثروة الزراعية والحيوانية). - تقدير الكلفة البيئية من خلال حساب التراجع في نوعية حياة الناس وتردي نوعية البيئة مثل التعرض للأمراض الناتجة عن تلوث البيئة وكلفة علاج هذه الأمراض جسدياً وسنوات العمل والحياة التي تتم خسارتها بسبب الأمراض, إضافة إلى خسارة قيمة الخدمات البيئية والموارد وخاصة غير المتجددة منها, وكذلك خسارة الفرص والميزات البيئية مثل المعايير الجمالية للمناطق السياحية. وقد أوصت الدراسة بأن تتبنى الاستراتيجيات الصناعية في سورية سياسة التنمية الصناعية المستدامة، أي تشتمل بشكل متكامل وشامل على البعد البيئي عند إقامة أي مشروع تنموي صناعي. وذلك تماشيا مع مفهوم التنمية المستدامة التي تطالب المنشآت على اختلاف أنواعها بالحفاظ على أصول وموارد المجتمع البشرية والمادية والبيئية التي تعد ملكا للأجيال الحالية والمستقبلية. The study aimed to clarify the economic concept to the problem of environmental pollution and the economic effects of him. How is the confrontation of this economic problem through the following steps: 1- Quantification of environmental pollution (air quality monitoring in the surrounding medium). 2- Quantification of the results of environmental pollution (the negative impact on health and property due to air pollution , and loss of agricultural and animal wealth . 3- Estimate of the results of environmental pollution ( the cost of treatment and alternative employment opportunities , loss of GDP as a result of the inability to work due to illness or disability or early death , property damage costs in agricultural and animal wealth , the cost of damage in the aesthetic value . The study concluded that a range of results, including : • Monitoring and Pollution reality in Banias , and then compare the average cost incurred by the population as a result of ( health damage , property damage, damage in agricultural and animal wealth ). • Determination of environmental costs through the expense of a decline in the quality of people’s lives and the deterioration of the quality of the environment , such as exposure to diseases caused by environmental pollution and the cost of treating these diseases physically and years of work and life that are lost due to disease , in addition to the loss of the value of environmental services and resources, especially non-renewable ones, as well as the loss opportunities and environmental features such as the aesthetic standards of the tourist areas . The study recommended that the industrial strategies in Syria adopt Sustainable Industrial Development Policy, which include an integrated and comprehensive environmental dimension in the administration of any industrial development project . This is in line with the concept of sustainable development, which calls for enterprises of different types to preserve the assets and resources of the community of human, material and environmental which is considered the property of the current and future generations.